Challenges of engagement with health services in Sweden's schools: listening to the views of school nurses and students with recurrent pain. (2nd January 2016) - Rosvall, Per-Åke; Nilsson, Stefan
Abstract: This article reports on the views of school nurses ( n  = 25) and students with recurrent pain ( n  = 24) in Sweden with regard to school-based pedagogic practices. A number of common categories with implications for pedagogic practice were identified by analysing qualitative interviews with these groups, using the coding techniques of grounded theory. The results indicate that a failure to develop trust made it difficult for some students to initiate contact with a school nurse and that some students perceive the issue of recurrent pain being of relevance to all young people, deserving coverage in the curriculum. We thus conclude that it is important to integrate personal, social and health education in the ordinary spaces of teaching and learning in order to complement and bolster the conventionally organised school health services in Sweden. However, this might be difficult to achieve because many of the school nurses emphasised that health and education were commonly treated on parallel tracks in their schools, under the management of different authorities.